The assistance regulation of users of the Unique Health System (SUS) classified as non-urgent in an emergency hospital in the municipality of Belem do Para: Integrative revision (Research, Society and Development, 2021)
The study aims to review the scientific literature taking into account the interest in independent studies on public policy, outpatient care, demands and classification, in order to contribute to the quality of care provided to users of urgent and emergency health services classified as non-urgent. The methodological procedures adopted considered the six phases of integrative review proposed by Ganong, (1987) and consulted PubMed and the Virtual Health Library from the Scielo, Medline and Lilacs databases. As a result, 27 (twenty-seven) articles from the years 2015 to 2020 were obtained, 20 (twenty) of which were included in the study and among them 10 from 2018 to 2020. 7 (seven) articles were excluded because they deal with review and quantitative studies and the remaining 20 (twenty) were divided into 3 levels of evidence which are: 14 (fourteen) with level 4 or evidence from descriptive studies (non-experimental) or with a qualitative approach, 2 (two) at level 5 or evidence from reports of case or experiences and 4 (four) at level 6 that are evidence based on expert opinions. The studies have shown the need for greater investment in urgent and emergency issues in all points of health care, mainly in primary care as the coordinator of the care process; that the family members and users of the services emphasize the need for welcoming, risk classification and resolution in the care of health professionals and services; that the care regulation process needs to advance in the role of integrating health care levels and finally that the SUS is an unfinished health policy that needs evaluation, and investment because despite its advanced legislation to achieve its principles doctrinal and operational aspects have allowed space to consider health as a consumer good.